Tracing the Mythic Journey in James Joyce’s A Portrait of the Artist as a Young Man and Ulysses - Faisal, Hafiz Shahriar (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.